Implementasi Program SAKINAH dalam Meningkatkan Literasi dan Inklusi Keuangan Syariah pada Santri Pondok Pesantren Nurul Abshor Kabupaten Katingan - Siona Putri Shia Vanessa; Andrianto Suhada; Ferry Christian; Leliana Maria Angela (Jurnal Pengabdian Masyarakat Nusantara, 2026)
Sharia financial literacy is an important aspect in supporting inclusive and sustainable economic development. However, the level of sharia financial literacy among Indonesian society is still relatively low. This condition creates opportunities for Islamic boarding schools (pesantren) to play a strategic role in improving young generations’ understanding of financial management based on sharia principles. Therefore, this community service activity aimed to enhance the sharia financial literacy and inclusion of students through the SAKINAH (Santri Cakap Literasi Keuangan Syariah) Program at Nurul Abshor Islamic Boarding School, Katingan Regency. The program was implemented using a participatory educational approach through socialization, interactive discussions, simple simulations, and participant evaluations. The activity was carried out through collaboration among the Financial Services Authority (OJK) of Central Kalimantan Province, the Islamic Economic Society of Katingan Regency, PT Bank Syariah Indonesia Palangka Raya, Nurul Abshor Islamic Boarding School, the Regional Financial Access Acceleration Team of Katingan Regency, and students of Palangka Raya University. The results showed an improvement in students’ understanding of the importance of saving, the ability to distinguish between needs and wants, sharia financial management, and knowledge of legal and trustworthy sharia financial products and services. The SAKINAH Program was also considered effective in encouraging students to become agents of sharia financial literacy within the pesantren environment and the wider community.